Kritik Historis terhadap Konsep “Mencari Keadilan pada Orang Tidak Benar” dalam 1 Korintus 6:1-9a - Jefri Andri Saputra (Jurnal Apokalupsis, 2022)
This research is motivated by the encounter between the diversity of alternative conflict resolutions in Indonesia, ranging from state courts, customary courts, and church pastors, with Paul's criticism of the implementation of conflict resolution outside the church in Corinth. Therefore, the author aims to interpret Paul's criticism in 1 Corinthians 6:1-9a, so that it is not misinterpreted as a rejection of various alternative conflict resolutions in Indonesia. The author analyzes this text using a historical critical approach. The author assumes that the historical conditions in the writing of the epistle of 1 Corinthians is the motive for Paul’s criticism. At the end of this paper, the author finds that Paul's criticism in the text of 1 Corinthians 6:1-9a does not reject the existence of state and customary courts but seeks to summon the church to play a role in preventing, minimizing, and carrying out conflict resolution by implementing Christian values.